HUBUNGAN KEPERCAYAAN DIRI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI MAN 3 PADANG PANJANG - Nadira Safira; Iltavia Iltavia; Afnelli Zen (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this research is to see whether there is a link between a person's self-confidence and the assessment of mathematics learning outcomes for students of class XI MAN 3 Padang Panjang. The research population is students of class XI MAN 3 Padang Panjang with a sample of 40 students, with data collection using a random technique. . This research is a quantitative correlation research with the variable under study is the independent variable (x) is self-confidence while the dependent variable (y) is an assessment of learning outcomes in mathematics. Data collection was carried out using a questionnaire and the results of the odd semester MID exam for the 2022/2023 school year. after doing the calculation through the correlation test obtained r as much as 0.77 so that the relationship between students' self-confidence regarding learning outcomes is strong and unidirectional (positive). That way learning outcomes will increase if self-confidence also increases and vice versa. Based on the significance test also states that t count (7.44) > t table (2.024) thus the relationship between variable x and variable y has a significant influence, with a determination coefficient obtained of 69.4% while the rest is influenced by several other factors. Keywords: Self Confidence, Student Learning Outcomes, Mathematics.